Compression behaviours of concrete-filled Q690 high-strength steel tubular columns at low temperatures. (December 2021) - Yan, Jia-Bao; Luo, Yan-Li; Liang, Chen; Lin, Xuchuan; Luo, Yun-Biao; Zhang, Lingxin
Abstract: Concrete-filled high-strength steel tubular columns (CFHSTCs) were developed using high-strength steel (HS) Q690 for cold-region engineering constructions. To study their compression behaviours at low temperatures, 15 CFHSTCs were tested under axial compression at different low temperatures within 20 ~ −90 °C. Including the influence of low temperatures, the effects of steel-tube wall thickness was also covered in this study. Compression test results showed that under the condition of low temperatures, local buckling of HS tube (HST), core crushing and weld fracture of HST occurred to the CFHSTCs. The CFHSTCs achieved the compression capacity as the crushing of concrete core, and HST local buckling at the recession working stage. Decreasing temperatures from 20 to −90 °C improved ultimate compression capacity and elastic stiffness of CFHSTCs. Moreover, enlarging the wall thickness of HST improved compression behaviours of CFHSTCs both at ambient and low temperatures. This paper also developed 3D finite element model (FEM) to simulate low-temperature compression behaviours of CFHSTCs. Validations of the FEM simulation results against 15 tests confirmed its capacity on simulating compression behaviours of CFHSTCs at both ambient and low temperatures. Graphical abstract: Unlabelled Image Highlights: Lowing down temperature to −90 °C improved compression capacity of CFST with Q690 HS by 30% Lowing down temp from 20 °C to −90 °C reduced ductility of CFST with Q690 HS by 20% Local buckling of Q690 HS and concrete crushing occurred to CFST at low temperatures Developed FEM predicted well axial compression behaviour of CFST with Q690 HS